The use of Azoles Containing Natural Products in Cancer Prevention and Treatment: An Overview - Jabir, Nasimudeen R.; Firoz, Chelapram K.; Bhushan, Ashish; Tabrez, Shams; Kamal, Mohammad A. (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background & Objective: Cancer is one of the leading causes of death worldwide. In view of ever increasing number associated with cancer related death, there is an urgent need to find out a novel compound especially of natural origin (better efficacy, less or non-toxic and cost effective) that could serve against the treatment of all forms of cancer. Currently, available treatment options related to cancer have their certain limitations especially in the case of solid tumors. Method: In search of the natural anticancer compound, alkaloids, in general, have been exploited by the scientist working in this field of research. Among these alkaloids, azoles (secondary metabolite) have been significantly highlighted in literature because of their anticancer potential and better efficacy against various forms of cancer. Results: Their mechanism of action includes induction in the cleavage of poly-ADP ribose polymerase (PARP), induction of caspase 3 and caspase 9, modulation of nuclear factor kappa B, damage to DNA, cell cycle arrest at G1 and G2/M stage, apoptosis and c-Myb inhibition. In the current article, we have tried to cover various azoles especially from oxazoles, thiazoles and carbazoles class that have been reported for their anticancer potential. Conclusion: Based on our article, we believe that, soon, the scientific community will come up with certain azole which will work against cancer at large rather than a specific type of cancer.
Keywords: azoles